Antimicrobial Activities against Pathogenic Bacteria of Marine Actinobacteria Isolated from Mangrove Sediments at Klong Khon Mangrove Forest, Thailand - Mingma, Ratchanee; Tongtoht, Jetsda; Wongchawalit, Jintanart (Science Essence Journal, 2024)
The mangrove ecosystem is a complex structure that harbors a wide range of microbial communities, including marine actinobacteria that have significant potential for producing bioactive compounds with various biological functions. The investigation of mangrove-associated actinobacteria for antibacterial compounds reveals them as promising candidates for new antibacterial medications and presents opportunities for other biotechnological applications. The objective of this study was to examine the antibacterial properties of culturable marine actinobacteria from mangrove sediments of Klong Khon Mangrove Forest, Thailand. Fifteen actinobacteria were recovered and evaluated the antimicrobial activity using perpendicular streak method. Eight isolates showed the ability to inhibit the growth of Gram-positive bacteria Bacillus cereus TISTR 687 and Staphylococcus aureus ATCC 27853, with the inhibition zone ranging from 13.5±1.50 to 45.0±2.65 mm. Isolates KK20-01, KK20-27 and KK20-31 had the highest antimicrobial activity against pathogenic Gram-positive bacteria B. cereus TISTR 687 and S. aureus ATCC 27853, and were chosen to assess the antibacterial efficacy of the cell-free supernatant using the agar well diffusion method. All three isolates exhibited the capacity to suppress the growth of B. cereus TISTR 687, and were identified using 16S rRNA gene sequence analysis, which were found to be most closely related to Streptomyces olivaceus NRRL B-3009T (99.93% similarity), Streptomyces daghestanicus NRRL B-5418T (100% similarity) and Streptomyces parvulus NBRC13193T (99.42% similarity), respectively. Therefore, the sediments in the Klong Khon Mangrove Forest provided a rich source of streptomycetes exhibiting antibacterial properties. This demonstrates a great opportunity to carry out further investigation, considering the potential of marine actinobacteria to produce unique biologically active compounds